PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) SEKTOR TELLO - ARISKA, NUR; RIDWAN, RIDWAN (Patria Artha Management Journal, 2021)
This study aims to  determine the effect of Compensation and  Work Environment on Employee Performance at PT. PLN (Persero) Tello Sector.The analysis method used is using multiple regression analysis, namely to determine the effect of all independent variables, namely compensation and work environment, there are dependent variables, namely employee performance.The results of this study indicate that compensation affects the performance of employeeswho work at PT. PLN (Persero) Tello sector can be seen with the t value of 21.047 and the significance value of 0.000  (below 0.05)  which  means that compensation affects employee performance. The work environment has a significant effect on the performance of employees who work at PT. PLN (Persero) The Tello sector is seen by the t value of3.147 and the significance value of 0.003 (below 0.005), which means that the work environment variable also contributes in influencing employee performance. Simultaneously compensation and work environment significantly influence the performance of employees who work at PT. PLN (Persero) Tello sector is seen with a calculated F value of 510,651 with a significance of 0,000 (below 0.05).